2021
DOI: 10.1186/s12913-021-06239-0
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to enhance ward audit: a multi-site qualitative study

Abstract: Background Hospitals in many countries are encouraged to develop audits to assess and improve the quality of care. Ward audit is a specific form of audit and feedback that is commonly used but little studied. The aim of this study is to describe the content and application of hospital ward audit in order to identify potential enhancements to such audits. Methods Multiple qualitative methods were used to study a diversity sample of four English Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…We studied the impact of animations to increase the frequency with which two open-access papers [ 42 , 43 ] were accessed. In designing the intervention, we drew upon McGuire’s Persuasive Communication Matrix [ 22 ] to consider the source, channel, message, audience, and setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We studied the impact of animations to increase the frequency with which two open-access papers [ 42 , 43 ] were accessed. In designing the intervention, we drew upon McGuire’s Persuasive Communication Matrix [ 22 ] to consider the source, channel, message, audience, and setting.…”
Section: Discussionmentioning
confidence: 99%
“…The source was an applied health researcher, describing work undertaken as part of a PhD to describe and enhance audit and feedback. The work was undertaken with a supervisory team, and involved substantial stakeholder involvement through co-production and advisory groups [ 42 , 43 ]. The message of the first animation was a multisite description of what currently happens when a national audit reaches the hospital and how it could be enhanced through an intervention to support recipients to analyse performance, select strategies and generate commitment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies used team-level or unit-level measures (29,33,34,(39)(40)(41)(42)(43)(44)(45)(46)(47), facility-level measures (31,48,49) or practice-level measures (50). Six studies reported using individual-level data as feedback indicators (30,32,35,(51)(52)(53).…”
Section: Quality Appraisalmentioning
confidence: 99%
“…In some studies, feedback was provided in both written and verbal form, although very little detail was provided on the delivery (32,43,45,46,48,51). Three studies reported providing feedback only verbally (47,50,53). Two studies reported that feedback was provided in changing forms over the study period (44,57).…”
Section: Quality Appraisalmentioning
confidence: 99%